2020
DOI: 10.1371/journal.pone.0235253
|View full text |Cite
|
Sign up to set email alerts
|

When the killing has been done: Exploring associations of personality with third-party judgment and punishment of homicides in moral dilemma scenarios

Abstract: Killing people is universally considered reprehensible and evokes in observers a need to punish perpetrators. Here, we explored how observers' personality is associated with their cognitive, emotional, and punishing reactions towards perpetrators using data from 1,004 participants who responded to a set of fifteen third-party perspective moral dilemmas. Among those, four scenarios (architect, life boat, footbridge, smother for dollars) describing deliberate killings were compared to investigate the role of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 115 publications
(211 reference statements)
3
17
0
Order By: Relevance
“…Our finding that emotionality contributes to moral judgment is in line with the literature that used moral dilemmas in typical populations (Conway et al, 2018;Crockett et al, 2010;Greene et al, 2004;Suter & Hertwig, 2011) as well as with evidence of atypical moral judgment in subclinical or clinical populations with emotional deficits (Djeriouat & Trémolière, 2014;Karandikar et al, 2019;Patil & Silani, 2014b;. Alexithymia has for instance been associated with less concern for the victim (Patil & Silani, 2014a) and psychopathy has been associated with less concern over a victim's death (Behnke et al, 2020).…”
Section: Emotionality Modulates the Intent-based Process Of Moral Judsupporting
confidence: 89%
See 3 more Smart Citations
“…Our finding that emotionality contributes to moral judgment is in line with the literature that used moral dilemmas in typical populations (Conway et al, 2018;Crockett et al, 2010;Greene et al, 2004;Suter & Hertwig, 2011) as well as with evidence of atypical moral judgment in subclinical or clinical populations with emotional deficits (Djeriouat & Trémolière, 2014;Karandikar et al, 2019;Patil & Silani, 2014b;. Alexithymia has for instance been associated with less concern for the victim (Patil & Silani, 2014a) and psychopathy has been associated with less concern over a victim's death (Behnke et al, 2020).…”
Section: Emotionality Modulates the Intent-based Process Of Moral Judsupporting
confidence: 89%
“…Previous studies on moral dilemmas have found that greater deliberation was associated with greater acceptability of inflicting harm for utilitarian motives (Bartels, 2008;Behnke et al, 2020), and accepting harm as a mean to preserve the greater good was cognitively demanding (Greene et al, 2008;Suter & Hertwig, 2011;Trémolière et al, 2012). The present study complements this literature by suggesting that deliberative thinking may additionally modulate moral outrage following unfair or evitable harm, that is, when an agent harmed intentionally without utilitarian motives.…”
Section: Conscientiousness Increases Judgment Of Moral Wrongness Follsupporting
confidence: 70%
See 2 more Smart Citations
“…The authors found that increased recruitment of this network is associated with more blame towards the perpetrator. Besides this evidence in the general population, work in clinical populations has found that individuals with lower emotionality were more tolerant towards harmful outcomes (Behnke et al, 2020;Patil & Silani, 2014a). However, studies using moral transgressions in people low in emotionality found that these individuals were sometimes more severe, sometimes less severe towards the perpetrator depending on their intent (Djeriouat & Trémolière, 2014;Patil & Silani, 2014b;Trémolière & Djeriouat, 2016).…”
Section: Discussionmentioning
confidence: 99%